Synthesis and characterization of 3-(4-fluorophenyl)thieno[3, 2-b]thiophene and 3, 3'-(4- fluorophenyl)dithieno[3, 2-b;2', 3'-d]thiophene molecules. (10th September 2021) - Topal, Sema; Topal, Sebahat; Ulukan, Pelin; Ustamehmetoğlu, Belkıs; Ozturk, Turan; Sezer, Esma
Abstract: Synthesis of 3-(4-fluorophenyl)thieno[3, 2- b ]thiophene (FPhTT ) and 3, 3'-(4- fluorophenyl)dithieno[3, 2- b ;2', 3'- d ]thiophene (FPhDTT ) were achieved starting from 3-bromothiophene and 3, 4-dibromothiophene, respectively. They were electropolymerized and the resulting polymers P[FPhTT] and P[FPhDTT] were characterized by diverse electrochemical methods such as cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), galvanostatic charge-discharge (GCD), electrochemical quartz crystal microbalance (EQCM) and spectroelectrochemical measurements. Mechanism of electropolymerization of the monomers was supported by DFT level calculations. Band gaps of P[FPhTT] and P[FPhDTT] were calculated as 1.63 and 1.77 eV, respectively, from the onset absorptions of the absorption spectra. From EIS measurements, the highest capacitance values of P[FPhTT] and P[FPhDTT] were calculated to be 39.4 and 281.7 Fg 1−, respectively, when the applied potentials were equal to their oxidation peak potentials. Surface characterization of the P[FPhTT] and P[FPhDTT] films on ITO electrodes were performed by atomic force microscope (AFM) and the results suggested that P[FPhDTT] had more porous surface. GCD results indicated that P[FPhDTT] had higher energy density than P[FPhTT], possibly due to its porous structure. According to the ECD results, P[FPhTT] has more stable optical properties. As a conclusion, P[FPhDTT] might be suggested for energy storage applications while P[FPhTT] could be suitable for electrochromic devices.